La possibilité d’une Amérique - Carlos Pérez López (Nuevo mundo - Mundos Nuevos, 2008)
Beneath the surface of a certain historical continuum towards independence, there are a series of interruptions caused by heterogeneous political realisations concealed when the continent’s new nations were born. These series of interruptions made America shift between the possible and the impossible, between contingency and necessity, giving thus shape to the political map of the Continent depending on the success or the failure of several projects. Some were very ambitious (such as Bolivar’s), others rather modest. This is an America that has seldom seen daylight, overwhelmed by too many failed attempts. Could it be possible that the main reason behind the ever-present idea of independence is precisely a sort of founding obsession, whose traces -which we intend to explore here- are hidden in those very failures?